The validity and usability of markerless motion capture and inertial measurement units for quantifying dynamic movements - Edwards, N. A.; Caccese, J. B.; Tracy, R. E.; Hagen, J.; Quatman-Yates, C. C.; Oñate, J. (Medicine & Science in Sports & Exercise, 2025)
Purpose Motion capture technology is quickly evolving, providing researchers, clinicians, and coaches with more access to biomechanics data. Markerless motion capture and inertial measurement units (IMUs) are continually developing biomechanics tools that need validation for dynamic movements before widespread use in applied settings. This study evaluated the validity of a markerless motion capture, IMU, and red, green, blue, and depth (RGBD) camera system as compared with marker-based motion capture during countermovement jumps, overhead squats, lunges, and runs with cuts.